Effect of Moringa Leaves, Poultry Manure and NPK Fertilizers on Growth and Yield of Maize (Zea Mays L) in Ilorin, Southern Guinea Savannah of Nigeria (Global Journal of Science Frontier Research, 2018)
A field experiment was conducted in 2016 and 2017 planting seasons at the Teaching and Research Farm of Kwara State University, Malete, Nigeria to assess the growth and yield response of maize plant to organic and inorganic fertilizer. The study comprised of 6 treatments viz; Control, 100 % NPK 15-15-15, 100 % Moringa leaves (MO), 100 % Poultry manure (PM), 50% Moringa leaves (MO) + 50% NPK and 50% Moringa leaves (MO) + 50% Poultry manure (PM). All the treatments except the control were applied at the rate of 60 kg N/ha. The experiment was laid out in a randomized complete block design (RCBD) with 3 replications. Results showed that application of Moringa leaves with NPK at 4, 8 and 12 WAP significantly (p < 0.05) increased the growth parameters and grain yield of maize when compared to application of NPK, poultry manure and moringa leaves alone including the control treatment.
Keywords: growth; maize; moringa leaf; NPK; poultry manure; yield.